Information and communication technologies for adherence to antiretroviral treatment in adults with HIV/AIDS - Lima, Ivana Cristina Vieira de (2016)
Introduction: Information and communication technologies support interventions directed at the pre- vention of HIV transmission and patient monitoring by promoting improved accessibility and quality of care. Objective: To evaluate the efficacy of information and communication technologies in the adherence to antiretroviral treatment in adults with HIV/AIDS. Methodology: Systematic review conducted from March to May of 2015 in three databases—the Cumula- tive Index to Nursing and Allied Health Literature (CINAHL); the Latin-American and Caribbean Literature in Health Sciences (LILACS/BIREME) and SCOPUS; and the Cochrane library and the Medical Literature Analysis and Retrieval System Online portal (MEDLINE/PubMed). The sample consisted of nine random- ized clinical trials based on the use of information and communication technologies for adherence to antiretroviral treatment in adults with HIV/AIDS. Results: Three studies analysed the use of a short message service – SMS – two phone calls, two alarm devices, one web-enabled Hand-held device and one web electronic intervention. Improvements in the levels of adherence in the group subjected to the intervention were identified in seven studies. The phone was the type of information and communication technology with proven efficacy with respect to adherence. It was used to make calls, as well as to send alert messages and reminders about taking medications. Pagers were not considered to be effective regarding adherence to antiretroviral therapy. Conclusion: The integrated use of information and communication technologies with standard care pro- motes increased access to care, strengthening the relationship between patients and health services, with the possibility of mitigating the difficulties experienced by people with HIV in achieving optimal levels of adherence to drug therapy.